The value of the leukocytes phagocytic activity in the blood for the pathogenesis of the experimental allergic alveolitis in conditions of the adrenalin myocardial injury and correction of their violations by Tiotriazolini - Regeda, M. S.; Pyndus, V. B. (Journal of Education, Health and Sport, 2015)
Regeda M., Pyndus V. Значення фагоцитарної активності лейкоцитів у крові для патогенезу експериментального алергічного альвеоліту в умовах адреналінового пошкодження міокарда та корекція їх порушень Тіотриазоліном = The value of the leukocytes phagocytic activity in the blood for the pathogenesis of the experimental allergic alveolitis in conditions of the adrenalin myocardial injury and correction of their violations by Tiotriazolini. Journal of Education, Health and Sport. 2015;5(3):289-293. ISSN 2391-8306. DOI: 10.5281/zenodo.16454 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A289-293 https://pbn.nauka.gov.pl/works/551965 http://dx.doi.org/10.5281/zenodo.16454 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 12.03.2015. УДК 616.24 – 056.31 – 082.5 Значення фагоцитарної активності лейкоцитів у крові для патогенезу експериментального алергічного альвеоліту в умовах адреналінового пошкодження міокарда та корекція їх порушень тіотриазоліном The value of the leukocytes phagocytic activity in the blood for the pathogenesis of the experimental allergic alveolitis in conditions of the adrenalin myocardial injury and correction of their violations by tiotriazolini М. С. Регеда, В. Б. Пиндус M. Regeda, V. Pyndus Львівський національний медичний університет ім. Данила Галицького м. Львів, Україна Danylo Halytsky Lviv National Medical University Lviv, Ukraine Abstract Doctors are quite often faced with various combination of diseases; including there are cases of the allergic alveolitis that have been developed in the conditions of coronary heart disease. The question, concerning violations features of leukocytes phagocytic activity in blood and their role in pathogenesis of allergic alveolitis development against the adrenalin myocardial injury before and after application of the antioxidants has not been studied till now. Research objective was to find out changes of the leukocytes phagocytic activity in blood in dynamics of formation of the experimental allergic alveolitis and adrenalin myocardial injury, as well as to determine the influence of the tiotriazolini preparation on them. Experiments were carried out on 68 guinea pigs, which were divided into six groups. The first – control, the second, third, fourth and fifth groups – animals with the experimental allergic alveolitis and adrenalin myocardial injury respectively on the first, seventh, fourteenth and twenty fourth days of experiment. The sixth group – guinea pigs after application of the tiotriazolini, which was inserted intramuscularly once a day in a dose of 100 mg per1 kgof weight within 10 days (from 14 to 24 days). The gradual increase of level of the phagocytic index and phagocytic number in blood of animals in the 1st, 7th, 14th and 24th days of experimental allergic alveolitis development in the conditions of adrenalin myocardial injury has been determined during experiment. Application of the tiotriazolini caused corrective action on the specified indicators downwards. Thus, the conducted researches of indicators of the phagocytic index and phagocytic number in blood made it possible to study features of changes and to define an important role of leukocytes phagocytic activity in pathogenesis of experimental allergic alveolitis and adrenalin myocardial injury, as well as the positive correcting action of tiotriazolini on the specified markers has been established. Keywords: the experimental allergic alveolitis, adrenalin myocardial injury, leukocytes phagocytic activity, phagocytic index, phagocytic number, tiotriazolini. Ключові слова: експериментальний алергічний альвеоліт, адреналінове пошкодження міокарда, фагоцитарна активність лейкоцитів, фагоцитарний індекс, фагоцитарне число, тіотриазолін.